1999
DOI: 10.1046/j.1365-2168.1999.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of pneumatic dilatation in patients with dysphagia after antireflux surgery

Abstract: In this retrospective study pneumatic dilatation was effective and safe in nine of 16 patients with dysphagia following antireflux surgery. Peristalsis was normal in eight patients, in seven of whom it was associated with satisfactory results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Secondly, it is now recognized that early dysphagia (less than 2 months postoperatively) is present in a significant proportion of patients but settles with time without the need for intervention 11. The exception to this is in children who are less tolerant of dysphagia after laparoscopic fundoplication and hence are more likely to require early endoscopic dilatation 12. Two studies12,13 have shown dilatation success rates of 56 and 67%, respectively, in resolving postfundoplication dysphagia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, it is now recognized that early dysphagia (less than 2 months postoperatively) is present in a significant proportion of patients but settles with time without the need for intervention 11. The exception to this is in children who are less tolerant of dysphagia after laparoscopic fundoplication and hence are more likely to require early endoscopic dilatation 12. Two studies12,13 have shown dilatation success rates of 56 and 67%, respectively, in resolving postfundoplication dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…The exception to this is in children who are less tolerant of dysphagia after laparoscopic fundoplication and hence are more likely to require early endoscopic dilatation 12. Two studies12,13 have shown dilatation success rates of 56 and 67%, respectively, in resolving postfundoplication dysphagia. The study by Malhi-Chowla et al13 also found that the only symptom that responded to dilatation was dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…If dysphagia after fundoplication is very troublesome and not settling after 6 weeks, then oesophageal dilatation is often helpful [10]. In experience with 50 laparoscopic Nissen fundoplications at the Royal Hospital for Sick Children, Edinburgh, there was evidence of early dysphagia in 20%, two patients with near total dysphagia required early re-operation and conversion to a partial wrap, two underwent balloon dilatation and six were treated conservatively.…”
Section: Gastro-oesophageal Reflux Diseasementioning
confidence: 97%
“…Large-diameter (30-to 40-mm) pneumatic balloon dilation is effective for primary achalasia management [61,62]. Experience with this technique for persistent dysphagia following LARS is evolving and evaluable data remain limited [63][64][65][66][67].…”
Section: Balloon Dilationmentioning
confidence: 99%